2013
DOI: 10.1016/j.molcel.2013.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Kinetochores Coordinate Pericentromeric Cohesion and Early DNA Replication by Cdc7-Dbf4 Kinase Recruitment

Abstract: SummaryCentromeres play several important roles in ensuring proper chromosome segregation. Not only do they promote kinetochore assembly for microtubule attachment, but they also support robust sister chromatid cohesion at pericentromeres and facilitate replication of centromeric DNA early in S phase. However, it is still elusive how centromeres orchestrate all these functions at the same site. Here, we show that the budding yeast Dbf4-dependent kinase (DDK) accumulates at kinetochores in telophase, facilitate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
207
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(220 citation statements)
references
References 50 publications
(77 reference statements)
10
207
0
Order By: Relevance
“…1B). Conversely, the Ctf19 kinetochore protein advances pericentromeric origin firing by facilitating the modification of centromeric heterochromatin (Natsume et al 2013). The Fkh1 transcription factor also effects origin firing, delaying some origins and advancing others (Knott et al 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1B). Conversely, the Ctf19 kinetochore protein advances pericentromeric origin firing by facilitating the modification of centromeric heterochromatin (Natsume et al 2013). The Fkh1 transcription factor also effects origin firing, delaying some origins and advancing others (Knott et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…(B) The correlation between the firing time of origins, as determined by the firing-time parameter n from a quantitative analysis of replication kinetics ) and the number of MCM ChIP-seq reads in a 1-kb window around those origins. Blue dots represent origins repressed by telomere proximity (Lian et al 2011), Rpd3 (Knott et al 2009) activity, or Fkh1 (Knott et al 2012); red dots represent centromeric origins and other origins activated by Ctf19 (Natsume et al 2013); green dots represent all other origins. Chromosome 10 origins are indicated in orange; the origins used in Figure 2 and Supplemental Figure S2 are indicated in purple.…”
Section: Resultsmentioning
confidence: 99%
“…The existence of mechanisms that target Scc2/Scc4 to key chromosomal regions, such as pericentromeres, may explain why the modest peak of Scc2/Scc4 in late G 1 suffices in early cell cycle periods. Kinetochores directly mediate Scc2/Scc4 enrichment within pericentromeric chromatin, thereby ensuring the robust cohesion of sister chromatids that is vital for promoting chromosome biorientation, even under conditions in which cohesins are limiting (27,39,40). Perhaps more surprising given a previous report that Scc2 is not essential after S phase in the absence of DNA damage (7) are our observations that robust Scc2/ Scc4 chromatin association is achieved in G 2 /M cells and that post-S phase cell viability is reduced following Scc2 inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…However, it does not explain the regulation of the replication timing of individual chromosomal domains. Several recent studies showed that DDK is modulated in a chromosome loci specific form; for example, the Ctf19 kinetochore complex can recruit Dbf4 to the kinetochores in telophase to promote early DNA replication in S-phase (Natsume et al 2013). Then again, origins that fire late during S-phase, e.g.…”
Section: Ddk Dependent Regulation Of Dna Replication In Saccharomycesmentioning
confidence: 99%